Australian Housing Market Booms: Fundamentals or Speculation?*. Issue 315 (15th June 2020) - Shi, Shuping; Rahman, Arafat; Wang, Ben Zhe
Abstract : This paper investigates the presence of housing bubbles in Australia at the national, capital city and local government area (LGA) levels. We control for housing market demand and supply fundamentals using the technique of Shi (2017), and employ the recursive evolving method proposed by Phillips et al. (2015a, b) for the detection of explosive bubbles. While the national‐level analysis suggests a short‐lived bubble episode (2017Q3) over the entire sample period from 1999 to 2017, the results from the capital‐city‐level data reveal substantial heterogeneity across cities, with only short‐lived and isolated bubbles identified for Sydney and Melbourne during the recent rapid housing price expansions from 2013 to 2017. The LGA‐level analysis suggests that only a small percentage of LGA housing markets are identified to be speculative in Sydney and Melbourne from 2013 to 2017.